Heat Treatment and Its Effect on Tensile Strength of Fused Deposition Modeling 3D-Printed Titanium-Polylactic Acid (PLA) - Darsin, Mahros; Susanti, Rizqa Putri; Sumarji, Sumarji; Ramadhan, Mochamad Edoward; Sidartawan, Robertus; Yudistiro, Danang; Basuki, Hari Arbiantara; Wibowo, Robertoes Koekoeh Koentjoro; Djumhariyanto, Dwi (ComTech: Computer, Mathematics and Engineering Applications, 2024)
Titanium is a biocompatible metal commonly applied in biomedical fields such as bone and dental implants. Recently, the produced titanium-Polylactic Acid (PLA) filament for 3D printing Fused Deposition Modeling (FDM) technique is easier to operate and affordable. This filament contains less than 20% PLA, which is also biocompatible but hydrophobic and capable of producing inflammation of the surrounding artificial living tissue. Therefore, a heat treatment is needed to reduce or even eliminate PLA. The research aimed to optimize the mechanical properties and biocompatibility of titanium-PLA filaments through heat treatment, demonstrating significant advancements in 3D printing applications for biocompatible materials. A Thermogravimetric Analysis (TGA) was carried out to find out the right temperature for reducing PLA levels. Specimens were heat treated with four temperatures at 100oC, 160oC, 190oC, and 543oC, and two holding times of 60 and 120 minutes. The mass of the specimens was weighed before and after heat treatment to determine the mass reduction and tested for tensile, micrograph, and fractography observation. The result is a meagre mass reduction. The highest tensile strength of the heat-treated specimen with a heat treatment temperature of 160oC and a holding time of 60 minutes is 18.310 MPa. However, it is still below the strength of the non-heat treated specimen, 19.890 MPa. Specimens with low tensile strength have a microstructure that shows an uneven distribution of titanium particles. Last, fractography shows porosity in the specimens with the lowest tensile strength.